Transient expression of RhoA, -B, and -C GTPases in HeLa cells potentiates resistance to Clostridium difficile toxins A and B but not to Clostridium sordellii lethal toxin. - Giry, M (1995)
The bacterial pathogen Clostridium difficle synthesizes two high-molecular-weight toxins (A and B), which exhibit toxic effects in vivo and in vitro. Here, we present evidence that the major intracellular targets of these two toxins are the Rho GTPases. Overexpression of RhoA, RhoB, or RhoC GTPases in transfected HeLa cells conferred an increased resistance to toxins A and B, indicating that these toxins cause their cytopathic effects primarily by affecting Rho proteins. In addition, toxin A and B treatment appeared to result in modification of Rho, since Rho isolated from toxin-treated cells had a decreased ability to be ADP-ribosylated by Clostridium botulinum C3 exoenzyme. In contrast, the lethal toxin (LT) of Clostridium sordellii, although structurally and immunologically related to C. difficile toxin B, appeared to induce cytopathic effects independently of the Rho GTPases. Overexpression of RhoA in transfected HeLa cells did not protect them from the effect of LT, and Rho isolated from lysates of LT-treated cells was not resistant to modification by C3. Immunofluorescence studies showed that LT treatment caused a cytopathic effect that was very different from those described for C. difficile toxins A and B, resulting in an increase in cortical F-actin, with a concomitant decrease in the number of stress fibers, and in the formation of numerous microvilli containing the actin-bundling protein fimbrin/plastin.